Whipworms in humans and pigs: origins and demography. Issue 1 (December 2016) - Hawash, Mohamed; Betson, Martha; Al-Jubury, Azmi; Ketzis, Jennifer; LeeWillingham, Arve; Bertelsen, Mads; Cooper, Philip; Littlewood, D.; Zhu, Xing-Quan; Nejsum, Peter
Abstract Background Trichuris suis andT. trichiura are two different whipworm species that infect pigs and humans, respectively.T. suis is found in pigs worldwide whileT. trichiura is responsible for nearly 460 million infections in people, mainly in areas of poor sanitation in tropical and subtropical areas. The evolutionary relationship and the historical factors responsible for this worldwide distribution are poorly understood. In this study, we aimed to reconstruct the demographic history ofTrichuris in humans and pigs, the evolutionary origin ofTrichuris in these hosts and factors responsible for parasite dispersal globally. Methods Parts of the mitochondrialnad 1 andrrn L genes were sequenced followed by population genetic and phylogenetic analyses. Populations ofTrichuris examined were recovered from humans (n = 31), pigs (n = 58) and non-human primates (n = 49) in different countries on different continents, namely Denmark, USA, Uganda, Ecuador, China and St. Kitts (Caribbean). Additional sequences available from GenBank were incorporated into the analyses. Results We found no differentiation between human-derivedTrichuris in Uganda and the majority of theTrichuris samples from non-human primates suggesting a common African origin of the parasite, which then was transmitted to Asia and further to South America. On the other hand, there was no differentiation between pig-derivedTrichuris from Europe and the New World suggesting dispersal relates to human activities by transporting pigs and their parasites through colonisation and trade. Evidence for recent pig transport from China to Ecuador and from Europe to Uganda was also observed from their parasites. In contrast, there was high genetic differentiation between the pigTrichuris in Denmark and China in concordance with the host genetics. Conclusions We found evidence for an African origin ofT. trichiura which were then transmitted with human ancestors to Asia and further to South America. A host shift to pigs may have occurred in Asia from whereT. suis seems to have been transmitted globally by a combination of natural host dispersal and anthropogenic factors.